The MULTI-ACT model: the path forward for participatory and anticipatory governance in health research and care - Paola Zaratin; Deborah Bertorello; Roberta Guglielmino; Danilo Devigili; Giampaolo Brichetto; Valentina Tageo; Gabriele Dati; Stephanie Kramer; Mario Alberto Battaglia; Monica Di Luca (BMC, 2022)
Abstract The COVID-19 pandemic has unmasked even more clearly the need for research and care to form a unique and interdependent ecosystem, a concept which has emerged in recent years. In fact, to address urgent and unexpected missions such as "fighting all together the COVID-19 pandemic", the importance of multi-stakeholder collaboration, mission-oriented governance and flexibility has been demonstrated with great efficacy. This calls for a policy integration strategy and implementation of responsible research and innovation principles in health, promoting an effective cooperation between science and society towards a shared mission. This article describes the MULTI-ACT framework and discusses how its innovative approach, encompassing governance criteria, patient engagement and multidisciplinary impact assessment, represents a holistic management model for structuring responsible research and innovation participatory governance in brain conditions research.